All I want for Christmas is…Rigorous validation of predictive models to prevent hasty generalisations. Issue 6 (21st November 2019) - Mateen, Bilal; Sonabend, Raphael
Abstract : Bilal Mateen and Raphael Sonabend are searching for Santa Claus, armed only with a statistical model to predict ear size based on age. The plan sounds ridiculous, but there's a serious lesson here about the limits of predictive models Abstract : Bilal Mateen and Raphael Sonabend are searching for Santa Claus, armed only with a statistical model to predict ear size based on age. The plan sounds ridiculous, but there's a serious lesson here about the limits of predictive models.